Regulatory system of mGluR group II in the nucleus accumbens for methamphetamine‐induced dopamine increase by the medial prefrontal cortex - Meriem Haddar; Kyosuke Uno; Kohei Hamatani; Shin‐ichi Muramatsu; Atsumi Nitta (Wiley, 2019)
Abstract Aim We previously reported that methamphetamine (METH)‐induced conditioned place preference was attenuated by Shati/Nat8l overexpression in the medial prefrontal cortex (mPFC). Shati/Nat8l overexpression in the mPFC expressed lower levels of both glutamate and dopamine (DA) in the nucleus accumbens (NAc) and attenuated METH‐induced DA elevation. We suggested a mechanism in which a decline of glutamate levels in the NAc decreases extracellular DA levels. However, the hypothesis has not confirmed. Methods We conducted a recovery experiments by pre‐microinjection of an mGluR group II antagonist, LY341495, into the NAc shell of mPFC‐Shati/Nat8l‐overexpressed mice followed by METH injection and DA levels measurement by in vivo microdialysis. Results Pretreatment with LY341495 was able to restore METH‐induced DA increase. Furthermore, mice injected with an adeno‐associated virus vector containing GFP (AAV‐GFP vector) in the mPFC expressed a colocalization of GFP with DARPP‐32 a medium spiny neuron (MSN) marker. Next, co‐immunostaining of DARPP‐32 and neuronal nitric oxide synthase (nNOS: expressed in a subtype of gamma‐Aminobutyric acid (GABA interneurons) in ventral tegmental area (VTA) showed a colocalization of nNOS and DARPP‐32. Conclusion These results provided a proof that Shati/Nat8l attenuation of METH‐induced DA increase is mediated by mGluR group II in the NAc. Moreover, immunohistochemical study showed a direct connection of mPFC projection neurons with NAc MSN and a connection of MSN projection neurons with a subtype of GABA interneurons in VTA.